Achieving high flame retardancy, crystallization and biodegradability PLA based on 1 wt% addition of novel fully bio-based flame retardant. (14th October 2022) - Xu, Jian; Fei, Junhao; Tang, Tao; Ma, Meng; Shi, Yanqin; He, Huiwen; Chen, Si; Wang, Xu
Abstract: In this paper, a bio-based flame retardant PA-AR is synthesized, which endows PLA with good flame retardant and crystallization properties, and at the same time promotes the biodegradability of PLA. Only 1 wt% PA-AR makes the LOI value of PLA reach 26.8% and reaches UL-94 V-0 level. In addition, 1 wt% PA-AR increases the crystallinity of PLA to 23.4%, which increased by 460% compared with PLA. Further, due to the increase of crystallinity, the tensile strength is also improved. Besides, the addition of PA-AR can greatly promote the degradation performance of PLA under specific biological conditions. This work proposed a novel method to obtain completely biodegradable flame retardant composites. Graphical abstract: Image 1 Highlights: A bio-based compound is synthesized in aqueous phase as a flame retardant for PLA. 1 wt% addition of flame retardant can make PLA composite self-extinguish and enhance LOI value. The flame retardant endows PLA with excellent crystallization. The flame retardant significantly promotes the biodegradation rate of PLA.